2016
DOI: 10.1038/ncomms13210
|View full text |Cite
|
Sign up to set email alerts
|

Mixed functional microarchitectures for orientation selectivity in the mouse primary visual cortex

Abstract: A minicolumn is the smallest anatomical module in the cortical architecture, but it is still in debate whether it serves as functional units for cortical processing. In the rodent primary visual cortex (V1), neurons with different preferred orientations are mixed horizontally in a salt and pepper manner, but vertical functional organization was not examined. In this study, we found that neurons with similar orientation preference are weakly but significantly clustered vertically in a short length and horizonta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
58
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 64 publications
8
58
0
Order By: Relevance
“…In contrast, we observed pronounced local clustering on the <30 µm scale within each column, in which nearby neurons were more likely to share whisker tuning than predicted by chance, or than expected from the subcolumnar tuning gradient. Thus S1 appears similar to rodent V1, which contains microcolumn-like structures of co-tuned neurons on the 5-40 µm scale (Kondo et al, 2016;Ringach et al, 2016). Such clusters have not yet been found in auditory cortex (Bandyopadhyay et al, 2010;Issa et al, 2014;Panniello et al, 2018).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…In contrast, we observed pronounced local clustering on the <30 µm scale within each column, in which nearby neurons were more likely to share whisker tuning than predicted by chance, or than expected from the subcolumnar tuning gradient. Thus S1 appears similar to rodent V1, which contains microcolumn-like structures of co-tuned neurons on the 5-40 µm scale (Kondo et al, 2016;Ringach et al, 2016). Such clusters have not yet been found in auditory cortex (Bandyopadhyay et al, 2010;Issa et al, 2014;Panniello et al, 2018).…”
Section: Discussionmentioning
confidence: 88%
“…To determine if local clusters of similarly tuned neurons exist within the salt-andpepper map, as in V1 (Kondo et al, 2016;Ringach et al, 2016), we examined pairwise signal correlations (tuning similarity) for co-columnar neuron pairs. Signal correlation fell off with distance between paired neurons ( Figure 3A, red).…”
Section: L2/3 Pyr Neurons Show Heterogeneous Locally Clustered Tuningmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past decade the mouse has become an increasingly popular model system to study vision (1)(2)(3)(4)(5). Many defining characteristics of the murine cortical visual system are analogous to primates (6): They have retinotopically-organized, spatially-restricted receptive fields (4,7,8), a primary visual cortex that is the primary recipient of retinal input via the lateral geniculate nucleus in the thalamus (9), and multiple interconnected higher visual areas (2,10,11).…”
mentioning
confidence: 99%
“…The challenge has been greatest in rodents because of the long-held view that cortex lacks columnar organization (Ohki et al, 2005;. However, recent studies in mouse primary visual cortex (V1) have found that subcortically and intracortically projecting PNs are spatially clustered and are vertically aligned to mini-and microcolumns of cell bodies and dendrites with distinct tuning preferences (Kondo et al, 2016;Marukoda et al, 2017;Znamenskiy et al 2018).…”
Section: Introductionmentioning
confidence: 99%